Dynamic Changes in Host Gene Expression following In Vitro Viral Mimic Stimulation in Crocodile Cells - Sarker, Subir; Wang, Yinan; Warren-Smith, Brenden; Helbig, Karla J. (Frontiers in Immunology, 2017)
The initial control of viral infection in a host is dominated by a very well orchestrated early innate immune system; however, very little is known about the ability of a host to control viral infection outside of mammals. The reptiles offer an evolutionary bridge between the fish and mammals, with the crocodile having evolved from the archosauria clade that included the dinosaurs, and being the largest living reptile species. Using an RNA-seq approach we have defined the dynamic changes of a passaged primary crocodile cell line to stimulation with both RNA and DNA viral mimics. Cells displayed a marked up-regulation of many genes known to be involved in the mammalian response to viral infection, including viperin, Mx1, IRF7, IRF1, and RIG-I with approximately 10% of the genes being uncharacterised transcripts. Both pathway and genome analysis suggested that the crocodile may utilise the main known mammalian TLR and cytosolic anti-viral RNA signalling pathways, with the pathways being responsible for sensing DNA viruses less clear. Viral mimic stimulation upregulated the type I interferon, IFN-Omega, with many known anti-viral interferon stimulated genes also being upregulated. This work demonstrates for the first time that reptiles show functional regulation of many known and unknown anti-viral pathways and effector genes. An enhanced knowledge of these ancient anti-viral pathways will not only add to our understanding of the host anti-viral innate response in non-mammalian species, but is critical to fully comprehend the complexity of the mammalian innate immune response to viral infection